2019
DOI: 10.1002/humu.23937
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, neuroimaging and biochemical findings in patients and patient fibroblasts expressing ten novel GFM1 mutations

Abstract: Pathogenic GFM1 variants have been linked to neurological phenotypes with or without liver involvement, but only a few cases have been reported in the literature.Here, we report clinical, biochemical, and neuroimaging findings from nine unrelated children carrying GFM1 variants, 10 of which were not previously reported. All patients presented with neurological involvement-mainly axial hypotonia and dystonia during the neonatal period-with five diagnosed with West syndrome; two children had liver involvement wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(47 citation statements)
references
References 16 publications
1
46
0
Order By: Relevance
“…The present study demonstrated that the levels of NDUFA13 were decreased in the liver; however, they were unchanged in the kidney. This observation was not surprising given that the nuclear-encoded OXPHOS complex I protein NDUFA13 is unstable during complex I assembly and is compromised in mitochondrial translation deficiencies (12), possibly in a tissue-specific manner. Consistent with previous observations (11), the expression level of the OXPHOS complex II protein SDHB was not attenuated in the present study, due to the exclusive nuclear genetic origin of the complex.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The present study demonstrated that the levels of NDUFA13 were decreased in the liver; however, they were unchanged in the kidney. This observation was not surprising given that the nuclear-encoded OXPHOS complex I protein NDUFA13 is unstable during complex I assembly and is compromised in mitochondrial translation deficiencies (12), possibly in a tissue-specific manner. Consistent with previous observations (11), the expression level of the OXPHOS complex II protein SDHB was not attenuated in the present study, due to the exclusive nuclear genetic origin of the complex.…”
Section: Discussionmentioning
confidence: 97%
“…The association between GFM1 gene defects and the recessively inherited mitochondrial disorder of oxidative phosphorylation was first reported 15 years ago (3). Over the past decade, the number of families identified to have mutations in this gene is only 25 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). These patients demonstrated diverse phenotypes; however, the most prevalent clinical feature was liver disease, lactic acidosis, encephalopathy, feeding problems and failure to thrive (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, metabolic workup generally showed elevated lactic acid, as did the case in this study. Some cases also showed elevated (Barcia et al, 2020;Calvo et al, 2012;Ravn et al, 2015;Simon et al, 2017;Smits et al, 2011).…”
Section: F I G U R Ementioning
confidence: 98%
“…The younger brother had a genetic examination for amniotic fluid before delivery, and he was healthy. Black symbol represents the affected son and daughter by the GFM1 mutations; the arrow represents to the proband; and oblique stripe symbol represents patient with folate deficiency In a study concerning nine unrelated patients carrying GFM1 variants (Barcia et al, 2020), eight patients have compound heterozygous GFM1 mutations. The novel composition of two heterozygous mutations of GFM1 gene found in our study was c.679G > A and c.1765-2_1765-1delAG deletion.…”
Section: F I G U R Ementioning
confidence: 99%